Evaluation of nuclear dacryoscintigraphy in adult patients with dacryocystitis - Reddy, S. Chandrasekhara; Zakaria, Ahmad (1999)
Patency of lacrimal drainage apparatus was studied in 34 patients of chronic dacryocystitis (28 females and 6 males), aged between 16 and 82 years (mean age 53.2 years) using nuclear dacryoscintigraphy procedure. The watering of eyes was unilateral in 22 cases and bilateral in 12 cases. The postoperative status of the dacryocystorhinostomy procedure in one eye was assessed in 3 cases. The obstruction of nasolacrimal duct was noted in all the unilateral cases, however the obstruction of nasolacrimal duct in the unaffected eye was detected in 3 of these patients. In bilateral cases, the nasolacrimal duct obstruction was noted in both eyes in 4 cases, and in one eye only in 8 cases. There was partial obstruction of nasolacrimal duct in the other eye in these 8 cases. In all 3 postoperative cases the surgery was found to be successful as the new opening into the nasal cavity was patent. The mean time taken for the tracer material to reach the lacrimal sac was 7 seconds (range 5 20 seconds) The time taken for the tracer material to reach the nose in 18 unaffected control eyes in cases of unilateral epiphora patients was 6 minutes 20 seconds (range 1 minute 16 seconds to 12 minutes). Thus this non invasive, simple to do procedure was found to be very useful in the assessment of the patency of lacrimal drainage apparatus in patients with chronic dacryocystitis pre-operatively as well as post-operatively.The partial obstruction of nasolacrimal duct can be diagnosed easily by this procedure which can be missed by either syringing procedure or by contrast dacryocystopgram.